The administration of Muslim law in west Malaysia and the position of Syariah court / Janariah Abd Mutalib - Abd Mutalib, Janariah (Faculty of Law, 1986)
Before the British intervention Muslim Law and Adat were the law applied in the Malay States. The Sultan was the ruler where he possessed all the powers. If any dispute arise about the interpretation of the law and its disposition, the matters were be referred to him. He will give his decision base on Al-Quran, Al-Hadis and The Hukum Kanun which was enforced at that material time in every states. In Malacca there was Risalat Hukum Kanun and Undang-Undang Melaka. In verse it contained Muslim Law and Adat such as law relates to marriage, divorce, maintenance and others. In Pahang there was Hukum Kanun Pahang which contained Muslim Law relates to Qisas, forfeiture, defamation, robbery, theft and others. There was also law related to hire purchase, guarantee, investment, trust, land and gift. In Johore, Muslim Law which applied in Turki and Mesir/ Egypt was interprated in Malay and was adopted there.